2019
DOI: 10.1159/000503317
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Outcome of Two Different Regimes in Adhesive Capsulitis: A Prospective Clinical Study

Abstract: Significance of the Study• Idiopathic adhesive capsulitis is a painful disorder affecting up to 5% of the general population. • The variety of treatment modalities employed speaks for the fact that we still know little about the inciting etiology, pathogenesis, and response to treatment. • Our study concludes that physiotherapy plus intra-articular steroid injection is more effective compared to physiotherapy alone in pain control and improvement in range of motion at short-term follow-up. • More high-quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…However, the procedure can create pain due to the overdistention of the glenohumeral joint capsule. The pain that follows will prevent early shoulder manual exercise from achieving functional shoulder ROM [11,[16][17][18]. One rationale for using a nerve block in frozen shoulder treatment was to give early pain relief from the affected shoulder [1,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the procedure can create pain due to the overdistention of the glenohumeral joint capsule. The pain that follows will prevent early shoulder manual exercise from achieving functional shoulder ROM [11,[16][17][18]. One rationale for using a nerve block in frozen shoulder treatment was to give early pain relief from the affected shoulder [1,19].…”
Section: Discussionmentioning
confidence: 99%
“…The suprascapular nerve innervated ~70% of the shoulder [13,20]. Previous studies correlated earlier mobilizations with better outcomes in patients with frozen shoulders [17,18]. The hydrodilatation of the shoulder capsule with saline and corticosteroids was the mainstay treatment for patients suffering from symptomatic frozen shoulders.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these results, increased IGHL signal intensity in patients with AC can be considered as a maker for an early inflammatory disease stage, and is associated with inflammatory-type pain and limited ROM. Thus, the treatment of patients with such finding should be aimed at reducing (e.g., intra-articular corticosteroid injection, cryotherapy) or limiting (e.g., gentle physiotherapy) the capsular inflammatory process [33][34][35][36][37]. Previous studies demonstrated that MRI could not predict AC prognosis [21] or the outcome after capsular distension [38].…”
Section: Discussionmentioning
confidence: 99%
“…57,59,65,68,70,75,82,85 Four studies compared a multimodal program including exercises, with a multimodal program without exercises, 66, 78, 79, 86 and 24 studies compared two multimodal programs (identical PT modalities) including different exercises with each other. 56, 58-64, 66, 67, 69, 71-74, 76-78, 80, 81, 83, 84, 87, 88 Treatment period varied from 1 session 66 to 2 years 85 , with 4 weeks 61,63,72,73,75,84,86,88,89 as most common period. Other treatment durations were 2 weeks, 57,74,77,78,80 3 weeks, 59,64,79,87 5 weeks, 56, 65 6 weeks, 68, 69, 82 8 weeks 58, 62 and 12 weeks.…”
Section: Study Characteristicsmentioning
confidence: 99%